The Effectiveness of Giving A Combination of Ginger and Papaya Powder Drink in Reducing the Frequency of Nausea and Vomiting in Pregnant Women 12-16 Weeks - Desi Ratna Sari; Yanti Herawati; Udin Sabarudin (Indonesian Journal of Global Health Research, 2026)
Nausea and vomiting that occurs in early pregnancy is a common occurrence, it is due to an increase in the hormones estrogen, progesterone and the release of the hormone HCG (humanchorionic gonadothropin). Nausea and vomiting occur between 4 – 8 weeks and will continue for 14 -16 weeks. If this is not handled properly, it will harm the mother and fetus, because of a decrease in appetite resulting in a lack of electrolyte balance such as sodium, calcium, and potassium. The purpose of this study is to determine the effectiveness of jederasa powder drink in reducing nausea and vomiting in pregnant women at 12-16 weeks in the working area of UPTD Tanjung Baru Health Center, Ogan Komering Ulu Regency. This research employed a quantitative approach in the form of a pre-experimental study with a one-group pretest-posttest design. One group underwent pre- and post-treatment testing. The study focused on pregnant women experiencing emesis gravidarum symptoms. Only one group received treatment, and the results were then observed. Sampling was conducted using a purposive sampling technique based on previously identified population characteristics. Thirty-three respondents experienced nausea and vomiting. The study was conducted for 14 days, from September 27 to October 10, 2024. Data analysis used a paired sample t-test. The administration of jederasa powder drink showed the results of the frequency of nausea was known, the value of the "Paired Samples Test" showed a value of "Mean Paired Differences" of 3,303. This value shows the difference between the average Pre Test results and the average Post Test results, which is 9.45 –6.15 = 3,303. It is known that the value of Sig. (2-Tailed) is 0.000 <0.05. The results showed that there was an average difference between the results of the pretest and the posttest where there was an effect of giving jederasa powder drink in reducing the frequency of nausea in pregnant women at 12-16 weeks. Meanwhile, the results of the "Paired Samples Test" showed a "Mean Paired Differences" value of 3.818. This value shows the difference between the average pre-test results and the average post-test results, which is 7.03-3.21 = 3.818. It is known that the value of Sig. (2-Tailed) is 0.000 < 0.05. So it can be concluded that there is an average difference between the results of the pre test and the post test. Which means that there is an effect of giving a powdered drink. Jederasa powdered drinks are effective in reducing the frequency of nausea in pregnant women at the Tanjung Baru Health Center UPTD by 76%, reducing vomiting by 64% and jederasa powdered drinks can be accepted by more than 70% of pregnant women.